Phraseological units with onomastic component as a transfer of culture (German-Ukrainian parallels) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2019)
The article investigates phraseological units with onomastic component in Ukrainian and German linguoculture and correlations at language unit level / a transfer of culture. Types of connotative meaning that realize these units are characterized in the article. The ways of introducing them to the structure of phraseological units (rethought biblical names; derivatives of canonized baptismal names; names related to the cultural and historical path of Ukrainian and German nations) are clarified on the example of proper names. Emphasis is made on rethinking of biblical expressions in Ukrainian and German phraseological fields, corresponding unique vocabulary. The regularities of anthroponym using in phraseological units, that has an additional positive or negative colouring (rhythm-forming function, functionality, typing) have been established. The individualized proper names, that are used to indicate a certain phenomenon or characteristics of individual human traits / general characteristics of a temper; assessment of human behavior according to the code of ethics; reproduction of the nation's worldview (cognitive, emotional levels of the world’s knowledge) that act as a typing tool are considered. The usage statistics of certain male / female names, that are used as a structural-semantic component of phraseological units in Ukrainian and German, are given. The advantage of using male names in the studied language systems is stated. Thematic groups of phraseological units with an onomastic component, which characterize or present the laws of coexistence (family, community, society) as moral imperative, reproduce folk pedagogy (education of courtesy, diligence, etc.) are separated. Further research prospects of functioning features of phraseological units with onomastic component, which consist in the development of the translation methodology of direct / figured components are outlined.
Keywords: phraseological units; onomasticon; anthroponym; linguoculture; background vocabulary; interlingual phraseological correlates